Integrative medicine use in patients with cutaneous T-Cell lymphoma: A cross-sectional survey study. (September 2021) - Mahurin, Heather M.; Tarabadkar, Erica; Hippe, Daniel S.; Lachance, Kristina; Kim, Ellen J.; Loggers, Elizabeth T.; Shinohara, Michi M.
Highlights: A high percentage of patients with cutaneous T-cell lymphoma use integrative medicine for their disease. Nearly half of our patients reported using integrative medicine specifically to treat their lymphoma. The most common forms of integrative medicine therapies in our cohort were vitamins/minerals, prayer/meditation, and diet. Health-related quality of life was worse among patients who reported integrative medicine use. Abstract: Objectives: To characterize patterns of integrative medicine (IM) use and health-related quality of life (HRQoL) in patients with cutaneous T-cell lymphoma (CTCL). Design: Cross-sectional, online survey, created in conjunction with the Cutaneous Lymphoma Foundation (CLF). Setting: A link to the online survey was posted on the CLF Facebook page and emailed to the CLF listserv; 372 survey responses were received. Main outcome measures: The study outcomes were IM use, cancer symptoms, and HRQoL measured via the Skindex-16 and Functional Assessment of Cancer Therapy-General (FACT-G). Results: A total of 292 patient responses (66 % female, median age 59y) were included in analysis. 87 % had mycosis fungoides and 12 % had Sézary syndrome. A majority (59 %) of patients reported using IM for their CTCL, with 48 % using IM to treat their disease and 47 % using IM to manage their symptoms. The most commonly used IM were vitamins/minerals (32 %), prayer/meditation (26 %), diet (24 %), and exercise/yoga (22 %). Higher itch scores were reported by patients using IM compared to non-users (31 (IQR 10–62) and 18 (IQR 3–46) respectively; p = 0.002). HRQoL was worse among patients who reported IM use; median Skindex-16 scores were 54 (IQR 28–72) among IM users compared to 33 (IQR 19–57) for non-IM users (p < 0.001). Conclusions: IM use is common among patients with CTCL, particularly those with worse itching and worse HRQoL. IM interventions require further study given use by CTCL patients to treat disease and ameliorate symptoms.